The quest for fiscal rules - Lars P. Feld (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2018)
James Buchanan pioneered the political economics of public debt 60 years ago. In this paper, we contrast his thinking of the burden of debt, the public choice mechanisms that lead to excessive debt and the demand for constitutional restraints on public debt with its development, its sustainability, the evidence on the political economy of debt and on the effects of institutions. It turns out that Buchanan farsightedly anticipated the problems that would emerge from excessive indebtedness in the developed world. The introduction of fiscal rules appear as a late triumph of Buchanan's thinking. However, socialism is dead, but Leviathan lives on. Opposition to sound fiscal policies has increasingly dominated the public debates since the Great Recession.
Keywords: H6; E6; D72; K39; 330; James Buchanan; Public Debt; Fiscal Commons Problems; Fiscal Rules